2002
DOI: 10.1097/00024382-200211000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Ischemic Preconditioning Protects the Intestine and Reduces Bacterial Translocation

Abstract: Ischemic preconditioning (IPC) was first demonstrated in the heart, but this protective effect has been also recently described in the intestine. The aim of this study was to determine the effects of intestinal ischemic preconditioning on the morphology of intestine and bacterial translocation. Twenty-four male Wistar rats weighting 250 to 300 g were randomized into three groups. A control group of rats (n = 8) were subjected laparotomy. In an ischemic group (n = 8), laparotomy was performed and the superior m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 31 publications
3
54
0
9
Order By: Relevance
“…Aksoyek et al performed intestinal preconditioning for ten minutes and observed a reduction of BT for bloodstream, liver, spleen and mesenteric lymph nodes, corroborating our results 10 . As differential, the model used by us, characterized by a time scale of preconditioning of two, five, ten and 15 minutes, showed that the greatest reduction of serum cytokines and BT occurred at 15 minutes.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Aksoyek et al performed intestinal preconditioning for ten minutes and observed a reduction of BT for bloodstream, liver, spleen and mesenteric lymph nodes, corroborating our results 10 . As differential, the model used by us, characterized by a time scale of preconditioning of two, five, ten and 15 minutes, showed that the greatest reduction of serum cytokines and BT occurred at 15 minutes.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 91%
“…Based on the fact that ischemic preconditioning attenuates the tissue injury caused by ischemia-reperfusion, Aksoyek et al 10 demonstrated in an experimental model, in which rats were subjected to ischemic preconditioning ten minutes prior to sustained ischemia, that BT was lower than in those animals that had not undergone preconditioning. Although most reports in the literature using the time of ten minutes in ischemic preconditioning of the small intestine of rats, the optimal protocol of intestinal preconditioning in these animals, including the short ischemia time, is not yet well established 5,11 .…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Second, previous studies by other groups [7,8] also showed that 60 min ischemia followed by 60 min reperfusion in the same rat model as used in our study could cause severe intestinal injury, which was evidenced by significant morphological changes and mucosal cell apoptosis. Also, in our study, a preconditioning strategy of 10 min ischemia and 10 min reperfusion could significantly alleviate intestinal injury, which was in accordance with the previous report [9,10].…”
supporting
confidence: 93%
“…İskemik önkoşullamanın mukozal permeabiliteyi azalttığı, en önemlisi intestinal epitelyal apoptozisi önlediği, mezenterik venöz kanda CO 2 birikimini ve bakteriyel translokasyonu azalttığı gösterilmiştir (26)(27)(28)(29)(30) . İntestinal sistem önkoşulla-masının mekanizmasında nitrik oksit (NO), adenozin A1 reseptörleri, PKC, serbest radikaller ve opioidler önemli rol oynarlar (30)(31)(32) . Önkoşullama iskelet kasında da koruyucu etkiye sahiptir ve bu koruyucu etkisini iskelet kasındaki mitokondriyal KATP kanalları aracılığıyla gösterir (33) .…”
Section: Mi̇yokard Dişi Doku Ve Organlarda İskemi̇k öNkoşullamaunclassified